Maqasid Sharia Analysis of The Welfare Level of Muslim’s Ceramic Craft in Plered Purwakarta - Sunjoto, Arie Rachmat; Khoirunnisa, Farah; Afif, Mufti (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2023)
Introduction: The activity of making ceramics is a work that has been passed down from generation to generation from the ancestors of the Plered people until now. Amid its existence, the number of craftsmen in 2019 decreased to 163 from the previous number of 205 craftsmen. This study aims to determine Muslim ceramic craftsmen’s welfare level in the review maqaá¹£hid syari'ah in Plered District, Purwakarta Regency. Research Methods: Research data sources are primary and secondary data. A sample of 114 craftsmen was obtained through the Simple Random Sampling technique. Data collection techniques are observation, documentation, and questionnaires. The analysis technique used is a quantitative descriptive analysis technique with a percentage formula through a Likert scale assessment tool. Results: The results of this study indicate that overall Muslim ceramics craftsmen who are classified as high welfare criteria are 38 people (33.3%), 74 people (64.9%) are at the moderate welfare level, 2 people (1.8%) are classified as low welfare level, and there are no craftsmen with very low or very high welfare criteria. The determinants of the level of welfare of Muslim ceramic craftsmen are through hifdzu din, hifdzu nafs, hifdzu 'aql, hifdzu nasl, and hifdzu maal. In this case, the indicator of asset maintenance (hifdzu maal) the majority of craftsmen belong to the highest welfare criteria compared to other indicators, which is 95 people (83.3%).